Ability of greater duckweed (Spirodela polyrrhiza) to absorb cadmium and its potency as phytoremediator - Anca Awal Sembada; Teguh Adhitia Suyadi (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2022)
Phytoremediation is a method that uses the ability of plants to absorb pollutants in the environment both on land and in water. This study aims to explore duckweed which is a candidate for phytoremediator. Duckweed is a small aquatic plant that grows very fast. In this study, duckweed used is Spirodela polyrrhiza and cadmium was chosen as a model pollutant with concentrations of 0.05 and 0.1 ppm. Cultivation was done for 7 days. The specific growth rates in the 0.05 and 0.1 ppm treatments were decreased, 0.118±0.001 and 0.11±0.002 days-1, respectively, when compared to the control, 0.143±0.002 days-1. S. polyrrhiza was able to absorb cadmium with absorption capacity of 66.4 and 67.2 % at 0.05 and 0.1 ppm, respectively. These showed the potential of duckweed to be further developed as a phytoremediator for the environment.